2022
DOI: 10.3389/fcvm.2022.836392
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon Ablation for Treatment of Atrial Fibrillation in a Chinese Population: Five-Year Outcomes and Predictors of Recurrence After a Single Procedure

Abstract: BackgroundThe 5-year outcomes and predictors of atrial fibrillation (AF) recurrence following cryoballoon (CB) ablation in Chinese population remain scarce. Our aim was to report 5-year outcomes and predictors of AF recurrence following a single CB ablation procedure in a Chinese population.MethodsFrom December 2013 to August 2016, we included 256 consecutive patients (mean age: 58 ± 10.9 years old; female: 41.0%) with paroxysmal or persistent AF successfully underwent first-generation CB ablation at Fuwai hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The low number of perioperative complications may be related to the simplicity of cryo-balloon ablation and the short operative time because the short operative time in elderly patients is important to reduce complications. The incidence of venous access complications due to cryo-balloon PVI was previously reported to be 1.79–2.3%, 7 , 21 and the rate of puncture complications in the elderly group in this study was 1.2%. The success rate of the LAAC implantation in this study was 100%, and no perioperative major bleeding events were detected.…”
Section: Discussionsupporting
confidence: 51%
“…The low number of perioperative complications may be related to the simplicity of cryo-balloon ablation and the short operative time because the short operative time in elderly patients is important to reduce complications. The incidence of venous access complications due to cryo-balloon PVI was previously reported to be 1.79–2.3%, 7 , 21 and the rate of puncture complications in the elderly group in this study was 1.2%. The success rate of the LAAC implantation in this study was 100%, and no perioperative major bleeding events were detected.…”
Section: Discussionsupporting
confidence: 51%
“…The subjects included in the 19 studies were AF patients who underwent cryoablation, 7–25 of which eleven were prospective and the other eight were retrospective. The mean/median follow‐up period ranged from 38 to 124 months, incidence of recurrence and/or adverse events during the follow‐up period were provided.…”
Section: Resultsmentioning
confidence: 99%
“…It is characterized by atrial fibrosis resulting from a variety of cardiac insults that share common fibroproliferative signaling pathways. In addition, patients of persistent AF tend to have longer duration of AF and heavier AF burden, 8,13,19 which contributed to recurrence. Moreover, previous studies have explored scoring systems for the effectiveness of CB for atrial fibrillation, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryoballoon technology, preferred over traditional radiofrequency ablation, is known for its consistent, predictable outcomes and reduced complication risks. Long-term clinical studies [ 29 , 30 ] have confirmed the safety and efficacy of cryoballoon technology, demonstrating high success rates over 5 years and indicating its growing importance as a treatment option in AF therapy. The emergence of “PFA” by 2020 suggests the potential impact of this innovative technology.…”
Section: Discussionmentioning
confidence: 99%